2022
DOI: 10.3389/fphar.2022.977025
|View full text |Cite
|
Sign up to set email alerts
|

The expression and significance of efferocytosis and immune checkpoint related molecules in pancancer samples and the correlation of their expression with anticancer drug sensitivity

Abstract: Background: The efferocytosis-related molecules have been considered to be correlated with the resistance to cancer chemotherapy. The aim of this study was to investigate the expression and significance of efferocytosis-related molecules in cancers and the correlation of their expression with anticancer drug sensitivity, and provide new potential targets and treatment options for cancers.Methods: We investigated the differential expression of 15 efferocytosis-related molecules (Axl, Tyro3, MerTK, CX3CL1, Tim-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Arginine from ACs is transformed to putrescine to activate RAC1 to promote continual efferocytosis ( 45 ), and this arginine metabolism can be regulated by 3,3′-diindolylmethane ( 202 ). Indoleamine-2,3-dioxegenase1 promotes the transformation of tryptophan to kynurenine, and the latter enhances the expression of IL-10 and transforming growth factor-β ( 203 , 204 ). Additionally, AC-derived methionine transforms to S-adenosylmethionine, and the latter contributes to enhancing the expression of transforming growth factor-β via DNA methyltransferase-3A ( 205 ).…”
Section: Regulatory Pathways and Molecular Mechanisms Of Efferocytosismentioning
confidence: 99%
“…Arginine from ACs is transformed to putrescine to activate RAC1 to promote continual efferocytosis ( 45 ), and this arginine metabolism can be regulated by 3,3′-diindolylmethane ( 202 ). Indoleamine-2,3-dioxegenase1 promotes the transformation of tryptophan to kynurenine, and the latter enhances the expression of IL-10 and transforming growth factor-β ( 203 , 204 ). Additionally, AC-derived methionine transforms to S-adenosylmethionine, and the latter contributes to enhancing the expression of transforming growth factor-β via DNA methyltransferase-3A ( 205 ).…”
Section: Regulatory Pathways and Molecular Mechanisms Of Efferocytosismentioning
confidence: 99%
“…However, the level of efferocytosis activity exhibited by macrophages in PDAC remains uncertain. 15,16 The proposed study aims to employ single-cell sequencing technology to examine the efferocytosis activity, transcriptional regulatory networks and cellular communication mechanisms between macrophages and tumour cells in the setting of PDAC. This methodology will facilitate our comprehension of the molecular and cellular connections that underlie this particular ailment, perhaps yielding significant insights into innovative therapy options.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that cancers can exploit efferocytosis, a kind of cell death, to advance cancer growth and evade immune system detection. However, the level of efferocytosis activity exhibited by macrophages in PDAC remains uncertain 15,16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase‐8, as a member of the cysteine protease family, activates during anoikis, augments cell death, and inhibits peritoneal dissemination of human GC cells [10]. Besides, immune checkpoint expression (including Tyro3, Gas6, MFGE8, Stab2, Tim‐4, CX3CL1, IDO1, Rac1, and PD‐L1) is directed against cancer cells to avoid immune attack, and they were associated with reducing the half‐maximal drug inhibitory concentration (IC50) for multiple anti‐cancer drugs [11]. Therefore, mining immunotherapeutic biomarkers and the role of epigenetics in gene regulation further assist GC patients in formulating precise immunotherapy regimens for durable efficacy.…”
Section: Introductionmentioning
confidence: 99%